2003
DOI: 10.1194/jlr.m200329-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxidized LDL forms complexes with β2-glycoprotein I: implication as an atherogenic autoantigen

Abstract: ␤ 2 -glycoprotein I ( ␤ 2 -GPI) is a major antigen for antiphospholipid antibodies (Abs, aPL) present in patients with antiphospholipid syndrome (APS). We recently reported ( J. Lipid Res ., 42: 697, 2001; J. Lipid Res. , 43: 1486, 2002) that ␤ 2 -GPI specifically binds to Cu 2 ؉ -oxidized LDL (oxLDL) and that the ␤ 2 -GPI ligands are -carboxylated 7-ketocholesteryl esters. In the present study, we demonstrate that oxLDL forms stable and nondissociable complexes with ␤ 2 -GPI in serum, and that high serum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 58 publications
5
151
1
5
Order By: Relevance
“…MHCII is believed to present exogenous antigens, but nearly 20-30% of antigens presented by APCs in a MHCII-dependent manner are self-antigens (38). Previous results showed that in atherosclerosis heat shock protein 60, oxidized LDL and b2-glycoprotein I act as self-antigens (39)(40)(41). During the onset of adipose expansion in obesity, oxidative stress and endoplasmic reticulum stress induce the generation of lipid-binding protein, oxidative modified protein, and misfolded protein, which might be the self-antigen to MHCII.…”
Section: Discussionmentioning
confidence: 99%
“…MHCII is believed to present exogenous antigens, but nearly 20-30% of antigens presented by APCs in a MHCII-dependent manner are self-antigens (38). Previous results showed that in atherosclerosis heat shock protein 60, oxidized LDL and b2-glycoprotein I act as self-antigens (39)(40)(41). During the onset of adipose expansion in obesity, oxidative stress and endoplasmic reticulum stress induce the generation of lipid-binding protein, oxidative modified protein, and misfolded protein, which might be the self-antigen to MHCII.…”
Section: Discussionmentioning
confidence: 99%
“…(37) , a incidência de IAM não-fatal foi dez vezes maior do que a esperada de acordo com a escala de Framingham, a de morte por DAC foi 17 vezes maior e a de acidente vascular encefálico teve aumento próximo de oito vezes. Com efeito, outros autores têm evidenciado novos fatores diretamente relacionados à inflamação sistêmica e possivelmente implicados no mecanismo de aterogênese acelerada, como a ativação do sistema complemento, inibição da lipoproteína lipase pela IL-6 (8) , anticorpos anti-HDL e anti-Ox LDL (10) , além da presença dos anticorpos antifosfolipídicos, que foram associados à reatividade cruzada com anti-HDL e anti-ApoA1, anti-OxLDL e à formação de complexos β2GP1-OxLDL (11,40,41) . Outros trabalhos estabeleceram relações entre doença cardiovascular e manifestações de atividade de doença, como pericardite (41) , vasculite digital (6) , aumento da VHS e da PCR (4) e leucopenia ou com escores mais elevados de SLICC (42) .…”
Section: Fatores De Risco Cardiovascularesunclassified
“…The role that apoptosis plays in the exposure of these phospholipids on the cell surface and the subsequent interaction with  2 GPI has been proposed as a possible mechanism for the production of pathogenic aPL in APS patients [30]. An interesting pathogenic role for oxidized low-density lipoprotein (ox-LDL)/ 2 GPI complexes bound by aPL in the initiation and progression of atherogenesis has been described [31,32].…”
Section: Antigenic Targets Of Antiphospholipid Antibodies: Phospholipmentioning
confidence: 99%